Training Program for Digital Marketing of Creative Business Products of Alu Village Community - Suhartina, Suhartina; Syah, Setiawan Putra; Susanti S, Irma; Sukoco, Hendro; Nuraliah, Siti; Irfan, Muhammad; Utami, Rahmawati Ning; Ikram, Zul; Pardi, Pardi; M. Masdi, M. Masdi; Aswin, Aswin (Asian Journal of Community Services, 2023)
The problems faced by the local community are: Lack of knowledge and skills of business actors in marketing their creative business products to a wider community outside the Polewali Mandar district area. The objectives and output targets to be achieved in this activity are that the partner village community can and is able to use social media and E-Commerce applications to market their creative business products or crafts independently and the number of sales of handicraft products and the income of the community of SME players in Alu Village, Alu sub-district increases. The method of implementing this service is the participatory counseling method; demonstration training method and practical activities by participants; and the method of mentoring and assisting community participants (creative business actors).